2012
DOI: 10.1007/s11033-012-1653-5
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and analysis of genes mainly expressed in adult mouse heart using subtractive hybridization cDNA library

Abstract: Subtractive hybridization cDNA library (SHL) is one of the powerful approaches for isolating differentially expressed genes. Using this technique between mouse heart and skeletal muscle (skm) tissues, we aimed to construct a cDNA-library that was specific to heart tissue and to identify the potential candidate genes that might be responsible for the development of cardiac diseases or related pathophysiological conditions. In the first step of the study, we created a cDNA-library between mouse heart and skm tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 34 publications
0
6
0
1
Order By: Relevance
“…This indicates that TOF may share common mechanisms with neurodegenerative disorders. However, the association between NDUFB and NDUFS family genes and TOF has seldom been reported, except for NDUFB5, which has been confirmed to be expressed in mouse heart tissues ( 35 ). Despite the lack of direct evidence, previous studies have supported a connection between TOF and neurodegenerative disorders.…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that TOF may share common mechanisms with neurodegenerative disorders. However, the association between NDUFB and NDUFS family genes and TOF has seldom been reported, except for NDUFB5, which has been confirmed to be expressed in mouse heart tissues ( 35 ). Despite the lack of direct evidence, previous studies have supported a connection between TOF and neurodegenerative disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Among many transcripts, the Midn transcript was previously isolated from a heart-specific SHL and data of our previous work were given elsewhere in detail (Komurcu-Bayrak et al, 2012). Briefly, we analyzed the data from the SHL by comparative screening through nucleotide and protein sequences in a gene database (http://blast.ncbi.nlm.nih.gov/Blast.cgi).…”
Section: Identification Of Midnolin Transcript From a Heartspecific Cmentioning
confidence: 99%
“…In the systematic bioinformatics analysis of our previously established heart-specific subtractive hybridization cDNA library (Komurcu-Bayrak et al, 2012), we detected a clone with 284 nucleotide length sequence that showed 96% homology to the 3'UTR of the mouse Midn gene (NM_021565.1; positions 3402-3682). According to the NCBI and Ensembl databases, the mouse Midn gene has three alternatively spliced transcripts (NM_021565, NM_001305798, and NM_001305799) that differ mainly in their 5' coding region and transcript variant 1 (NM_021565) encoding the longest isoform (NP_067540).…”
Section: Homology Of Shl Clone To Midn Transcriptmentioning
confidence: 99%
See 2 more Smart Citations